2020
DOI: 10.1080/19396368.2019.1701139
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of sperm used for IVP by three different separation methods with spatial light interference microscopy

Abstract: 2020) Morphometric analysis of sperm used for IVP by three different separation methods with spatial light interference microscopy, Systems Biology in Reproductive Medicine, 66:1, 26-36, ABSTRACTThe goal of this study was to characterize sperm populations resulting from three different methods of sperm selection used for bovine in vitro fertilization. We compared sperm selection with discontinuous Percoll gradients, Swim-Up, and electro-channel. Spatial light interference microscopy (SLIM) was used to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…It is conceivable that our approach would be especially useful when selecting among seemingly healthy sperm, with no obvious defects. We note that the assay of these relatively small ratios is made possible by the high sensitivity of SLIM (57,58). Importantly, in this work, we presented a template for automating the annotation of a large number of cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that our approach would be especially useful when selecting among seemingly healthy sperm, with no obvious defects. We note that the assay of these relatively small ratios is made possible by the high sensitivity of SLIM (57,58). Importantly, in this work, we presented a template for automating the annotation of a large number of cells.…”
Section: Discussionmentioning
confidence: 99%
“…PCA statistics have been used to determine the seminal traits affecting bull fertility [48], the differentiating factors of bull fertility [49], the role of seminal plasma proteins in sperm motility of buffalo [50], morphometric analysis of sperm by different separation methods [51], changes in bull semen metabolome concerning cryopreservation and fertility [52], the cellular and functional parameters on the freezability of sperm [53], proteomic and lipidomic tolerance of stored boar spermatozoa to autologous seminal plasma [54], and spermatozoa quantitative proteomics of human normozoospermia and asthenozoospermia [55]. To the best of our knowledge, using PCA to determine the fertility of post-thawed extended semen has never been studied.…”
Section: )mentioning
confidence: 99%
“…Even more when variations in sperm morphometry have been widely associated with fertility (reviewed by Maroto‐Morales et al (2016) and differentiation processes among breeds (Soler et al, 2017) and species (Martinez & Garcia, 2020; Vicente‐Fiel et al, 2013). Although the mechanism underlying such relationship is still unveiled, it has been shown that sperm head shape could affect sperm motility in several livestock species (Love, 2011; Malo et al, 2006; Rubessa et al, 2020), thereby affecting their ability to reach and penetrate the egg (García‐Vázquez et al, 2016). On the contrary, several comparative and experimental studies have failed to address the link between sperm morphology and motility, providing contradictory results even within the same taxa (reviewed by Simmons and Fitzpatrick (2012).…”
Section: Introductionmentioning
confidence: 99%